Formulating EFL Writing Lecturers' Expectations: Lessons from Islamic Tertiary Education during the COVID-19 Pandemic - Endah Kurtianti; Endang Setyaningsih; Nur Arifah Drajati (STAI Hubbulwathan Duri, 2021)
This research was designed to investigate which factors influenced the formation of lecturers’ expectations amid online learning during the COVID-19 outbreak in an Indonesian Islamic university. The recent study employed an exploratory case study by observing online EFL writing learning activities, interviewing the three lecturers, and collecting documents. The data was then analyzed qualitatively using an interactive model. Lecturers' expectations in this study were viewed from the key focus of expectation: feedback provided by lecturers. They established class-level expectations, not individual ones as primary and secondary levels. This study elucidates Islamic university lecturers' factors contributing to form expectations: lecturers’ past teaching experiences and teaching self-efficacy. Lecturers have not highly adjusted to any change that emerged in online learning. Accordingly, they have not shown firm belief in grouping students and assuring students’ originality in composing essays. At the same time, the students' demographic factors were motivation and gender. Female students showed higher motivation through participating more often during discussions. It yielded more learning feedback they received. Implications of this study were noted for self-reflection among lecturers to establish high expectations for students to enhance their learning.